LGBT DAN LIWĀT UMAT NABI LUTH DALAM PERSPEKTIF TAFSIR - Wahyu Ihsan; Umar Faruq Thohir (Institut Agama Islam Negeri (IAIN) Ponorogo, 2022)
In 2021-2022, many LGBT campaigns were found that were carried out openly, ranging from the realm of sports, politics, mass media to the realm of religion, by sharing campaign forms such as rainbow colored flags and rainbow colored stickers displayed in the public sphere and mass media. . Ironically, there are cases of great British protection in Jakarta and mosques in Germany flying rainbow colored flags, this proves that politics and religion have been possessed by the LGBT virus. The LGBT campaign has something to do with the story of the people of Prophet Lut AS being called same-sex lovers, his actions in Arabic terms liwat or fāhisah. They also commit acts openly to influence others to commit these heinous acts. The purpose of this research is to analyze the LGBT campaign with a historical approach to the story of the people of Prophet Lut As in the Qur'an. Verses about LGBT include: Q.S al-A'raf 80-81, Hud 78-79, Ash-Syuara 165, an-Naml 54-55 and al-Ankabut 28-29. The results of this research prove that the emergence of the LGBT campaign has something to do with the story of the people of Prophet Lut in the US due to environmental, psychological and theological influences. The impact of the LGBT campaign is very significant and the causes of the LGBT campaign openly include legal tolerance for LGBT actors and the existence of figures who openly voice LGBT. So, it's time for us, especially scholars, intellectuals, politicians, governments and even young people to immediately anticipate LGBT viruses or LGBT activists in their own ways so that they don't spread to the public sphere and mass media.